Women Leaders, Cybersecurity Disclosure & ESG Performance: Are Women More Cybersecurity-Aware? - Zainuddin, Zainuddin; Tjahjadi, Bambang (AIBPM Publisher, 2025)
This study investigates the effect of women leaders on ESG performance through the mediating role of cybersecurity disclosure. Employing a sample of 46 banks across ASEAN countries (Indonesia, Malaysia, the Philippines, Singapore, Thailand, and Vietnam) over the period 2017–2022, the study yields 242 firm-year observations. Cybersecurity disclosure was measured using content analysis, while data were analyzed using panel regression with robustness and additional tests to ensure consistency. The findings reveal that both women on boards and female chairpersons have a significant positive impact on cybersecurity disclosure, which in turn significantly enhances ESG performance. Furthermore, cybersecurity disclosure fully mediates the relationship between women leaders and ESG performance. This research confirms the relevance of Resource Dependency Theory and contributes by proposing a structured cybersecurity disclosure keyword framework for future studies. Practically, the findings urge stakeholders to increase the representation of women in both number and strategic leadership roles, and to integrate cyber risk into ESG metrics. The study also contributes to the achievement of SDG 5, SDG 8, and SDG 12.